Transformer Health Monitoring And Control Through Arduino - 1K.SRIDHAR; M.ASSARUDEEN; J.RANJITH KUMAR; E.SARATHBABU (International Journal of Advance Engineering and Research Development (IJAERD), 2018)
Our project is about design and implementation to monitor and record key parameters of a distribution transformer like load currents, oil level, voltage level and temperature. The idea of on-line monitoring system integrates with a stand alone Arduino and different sensors. It is installed at distribution transformer side and the above parameter are recorded using the ARDUINO Microcontroller. The obtained parameters are processed and recorded in the system memory. If any abnormality or an emergency situation occurs in the system, then the values will be displayed in the monitor according to some predefined instructions programmed in the microcontroller. This mobile will help the transformers to operate smoothly and identify problems before any catastrophic failure.